Sistem Informasi Pada Sanggar Dwipayana Nusantara Berbasis Web Dengan Menggunakan Reminder Email - Nadia Safira; Siti Nur Fitria Rachmawati (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
Sanggar Dwipayana Nusantara is a dance studio that provides rental facilities for various traditional costumes and dances. The business process at Sanggar Dwipayana Nusantara still uses manual methods, so that the studio has difficulty in cross-checking borrowing and returning data as well as student registration data for dance courses that are often lost. From the existing problems, it is necessary to build an information system for the website-based Dwipayana Nusantara Studio with a reminder feature via email. The method used for this research is an approach method by collecting data and data analysis techniques. The SDLC (Software Development Life Cycle) method is a system development method that can be used in this study. The result of this research is the construction of a costume rental information system and website-based dance course registration with a reminder feature which is expected to solve problems in data processing at Sanggar Dwipayana Nusantara. Keyword: information system; sanggar dwipayana nusantara; SDLC; reminder.